Genetic diversity of patchouli cultivated in Bali as detected using ISSR and RAPD markers - MADE PHARMAWATI; I PUTU CANDRA (Society for Indonesian Biodiversity, 2015)
Pharmawati M, Candra IP. 2015. Genetic diversity of patchouli cultivated in Bali as detected using ISSR and RAPD markers. Biodiversitas 16: 132-138. Patchouli is a bushy herb that has strong scent. Patchouli's oil is extracted from patchouli leaves and used asperfumes, incense and traditional medicines. Centre of patchouli cultivation in Bali is in Badung District, however it is also grown inother area such as Buleleng District. The patchouli plant from Aceh ((Pogostemon cablin (Blanco) Benth) is considered as a better plantspecies due to its high quality oil. Java patchouli (Pogostemon heyneanus) has lower quality. Molecular marker was used to detectdiversity of patchouli grown in Bali. Leave samples of patchouli from 12 areas in Badung and Buleleng District were collected. Theareas included Lemukih, Wanagiri, Pupuan, Belok, Mekarsari, Nungnung, Plaga, Sidan, Mengwi, Lukluk, Abiansemal and Jegu.Patchouli samples of Lhokseumawe, Tapak Tuan, Sidikalang and Java were obtained from Research Institute of Spices and MedicinalPlants, Bogor, Indonesia. DNA was extracted using CTAB buffer. Seven ISSR primers and five RAPD primers produced scorable bandsand used for diversity and cluster analyses. The dendrogram showed that patchoulis grown in Bali are group together, separated fromJava patchouli. This support observation based on leaf morphology, that they belong to Aceh patchouli. The patchouli grown in Balishowed low genetic diversity with Nei and Li’s similarity in the range of 0.857 to 0.989. Keywords: Bali, genetic diversity, ISSR, patchouli, RAPD